A Water‐Soluble ESIPT Fluorescent Probe with High Quantum Yield and Red Emission for Ratiometric Detection of Inorganic and Organic Palladium. Issue 5 (20th March 2015) - Gao, Tang; Xu, Pengfei; Liu, Meihui; Bi, Anyao; Hu, Pengzhi; Ye, Bin; Wang, Wei; Zeng, Wenbin
Abstract A novel fluorescent probe with a high quantum yield (0.41), large Stokes shifts (255 nm), and red emission (635 nm) was designed to detect all typical oxidation states of palladium species (0, +2, +4) by palladium‐mediated terminal propargyl ethers cleavage reaction in water solution without any organic media. The probe showed a high selectivity and excellent sensitivity for palladium species, with a detection as low as 57 nM (6.2 μg L−1).